Pengaruh Bagi Hasil, Biaya Promosi, Efisiensi Operasional Dan Ukuran Perusahaan Terhadap Jumlah Deposito Mudharabah - Nurhidayatus Sifki; Ibram Pinondang Dalimunthe (JAS (Jurnal Akuntansi Syariah), 2022)
This study aims to show the effect of profit-sharing, promotion costs, operational efficiency, and company size on the number of mudharabah deposits. This study includes quantitative using secondary data from Islamic commercial banks (ICB). The population of this study is ICB registered with the financial services authority (FSA) in 2015-2020. The sample selection used the purposive sampling technique. The sample was obtained from as many as 8 ICB for six years, so the total data was 48. The data analysis method used multiple linear regression with the help of e-views software. The results showed that profit sharing and company size positively and significantly affected the number of mudharabah deposits. Promotion costs and operational efficiency do not affect the number of mudharabah deposits. Simultaneously profit-sharing, promotion costs, operational efficiency, and company size affect the number of mudharabah deposits. This study can be a reference for ICB management in improving its performance, especially in enlarging ICB. Then increase the profit-sharing customers receive, so customers are more interested in depositing their funds in the ICB.